Trend 1980 - 2011. Energy Information Administration. International Energy Statistics: Renewables Consumption | Country: Faroe Islands | Indicator: Total Renewable Electricity Net Consumption (Billion Kilowatthours), 1980-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 004-014-034. - Energy Information Administration (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Energy Information Administration (2015). International Energy Statistics: Renewables Consumption | Country: Faroe Islands | Indicator: Total Renewable Electricity Net Consumption (Billion Kilowatthours), 1980-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 004-014-034. Dataset: Provides statistics on consumption of electricity generated by renewables by country, as available. Renewables are energy resources that are naturally replenishing but flow-limited. They are virtually inexhaustible in duration but limited in the amount of energy that is available per unit of time. Renewable energy resources include biomass, hydro, geothermal, solar, wind, ocean thermal, wave action, and tidal action. Consumption is reported as net consumption, which excludes the energy consumed by the generating units. The dataset provides data for 220 countries, as available, on energy-related metrics, including total and crude oil production, oil consumption, natural gas production and consumption, coal production and consumption, electricity generation and consumption, primary energy, energy intensity, CO2 emissions and imports and exports for all fuels. Data are sourced from Energy Information Administration research, as well as from national and international agencies, listed at http://www.eia.gov/cfapps/ipdbproject/docs/sources.cfm. Category: Energy Resources and Industries, International Relations and Trade Source: Energy Information Administration The Energy Information Administration (EIA), created by Congress in 1977, is an independent statistical and analytical agency within the United States Department of Energy. Its mission is to provide policy-independent data, forecasts, and analyses to promote sound policy making, efficient markets, and public understanding regarding energy and its interaction with the economy and the environment. http://www.eia.doe.gov/ Subject: Energy Consumption, Renewable Energy